Video text binarization using connected component level non-text filtering - Cho, Beom Geun; Kim, Shin Gon; Koo, Hyung (International Conference on Electronics, Information and Communication, ICEIC 2018, 2018)
In this paper, we present a video text binarization algorithm using connected component (CC) level filtering. We develop a three-step algorithm: estimate the polarity of text, extract text/non-text CCs with a retinex filtering method, and filter out non-text components. The proposed non-text CCs filtering is considering CCs stroke width and contrast. We conducted experiments on subtitles in TV programs and movies. Experimental results showed that the method outperforms conventional methods in terms of a pixel-level accuracy and a character/word recognition rate.
Keywords: Connected component; Conventional methods; Filtering method; Non-text filtering; Recognition rates; Retinex; Step algorithms; Stroke widths; connected components; retinex filtering; video text binarization